The Expansion of Emergency Powers: Social Conflict and the Military in Indonesia. Issue 3 (3rd July 2017) - Crouch, Melissa
Abstract: The exercise of emergency powers is always controversial. This article identifies the expansion of the type and scope of emergency powers through legislative reform. It does so by examining the Indonesian Law on Social Conflict 2012, which allows a state of social conflict to be declared at the national, regional or local level in response to social conflict, such as conflict between religious or ethnic communities. The deliberate choice of the term "state of social conflict", rather than "state of emergency", is an attempt to obscure the nature of these powers. Analysis of these powers and the debate that has ensued suggests that the law expands the types of situation in which powers usually only reserved for an emergency are used, and by delegating this power to local authorities, the law in effect amounts to the expansion of emergency powers. I suggest that this should lead to renewed focus on meaningful limits and checks on the exercise of power during times of emergency.